Virtual WLAN: Going beyond Virtual Access Points - Coskun, Hakan; Schieferdecker, Ina; Al-Hazmi, Yahya (Electronic Communications of the EASST, 2009)
Wireless nodes equipped with multiple radio interfaces open up new fields of application. Ranging from multi-channel usage in a cell in order to increase the bandwidth to the creation of meshed multi-hop topologies. Using multiple wireless cards demands a large physical space, more energy consumption and as a consequence decreasing in the battery lifetime. Virtualization of the wireless network interface, which means to use a single wireless network interface to connect to more than one network simultaneously, seems to be a promising approach, since it allows us to realize the mentioned scenarios only with one radio interface. In this paper, we want to shed light on the state of the art and want to introduce new approaches to push this field beyond the current status.